Acoustic Emission Simulation on Coal Specimen Subjected to Cyclic Loading - Huiqiang Duan; Depeng Ma (Advances in Civil Engineering)
The damage and failure state of the loaded coal and rock masses is indirectly reflected by its acoustic emission (AE) characteristics. Therefore, it is of great significance to study the AE evolution of loaded coal and rock masses for the evaluation of damage degree and prediction of collapse. The paper mainly represents a numerical simulation investigation of the AE characteristics of coal specimen subjected to cyclic loading under three confining pressures, loading-unloading rates, and valley stresses. From the numerical simulation tests, the following conclusions can be drawn: (1) The final cycle number of coal specimen subjected to cyclic loading is significantly influenced by the confining pressure, followed the valley stress. With the increase in confining pressure or valley stress, the cycle number tends to increase. However, the loading-unloading rate has a little influence on it. (2) The AE counts of coal specimen subjected to cyclic loading are greatly influenced by the confining pressure and the valley stress. With the increase in the confining pressure, the cumulative AE counts at the 1st cycle tend to increase but decrease at a cycle before failure; with the decrease in the valley stress, the cumulative AE counts per cycle increase in the relatively quiet phase. However, the loading-unloading rate has a little influence on it. (3) The failure mode of coal specimen subjected to cyclic loading is significantly influenced by the confining pressure. Under the uniaxial stress state, there is an inclined main fractured plane in the coal specimen, under the confining pressures of 5 and 10 MPa, the coal specimen represents dispersion failure. The loading-unloading rate and valley stress have little influence on it. (4) The AE ratio is proposed, and its evolution can better reflect the different stages of coal specimen failure under cyclic loading. (5) The influence of confining pressure on the broken degree of coal specimen subjected to cyclic loading is analyzed, and the higher the confining pressure, the more broken the failed coal specimen.